2015
DOI: 10.1111/his.12691
|View full text |Cite
|
Sign up to set email alerts
|

High c‐Met expression in stage I–II pancreatic adenocarcinoma: proposal for an immunostaining scoring method and correlation with poor prognosis

Abstract: Simplified c-Met expression is an independent prognostic marker in stage I-II PDAC that may help to identify patients with a high risk of tumour relapse and poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
5
9
0
Order By: Relevance
“…We divided all 70 PDAC patients into two survival groups (≤ or > median), using overall median survival (11.5 months, range 0.2 months ∼ 5 years) as a cut-off (Table 4). When markers between these two survival groups were compared, we found that tumors associated with poor survival had a strong trend towards having higher total c-MET level compared to those with better survival ( p = 0.05), resonating previous report showing c-MET to be frequently overexpressed and represents an independent poor prognostic factor in resected PDAC patients [18, 19]. Interestingly, patients with poor survival had significantly lower levels of p-SHC ( p = 0.002), p-PRAS40 (p = 0.002) and p-AKT ( p = 0.025).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We divided all 70 PDAC patients into two survival groups (≤ or > median), using overall median survival (11.5 months, range 0.2 months ∼ 5 years) as a cut-off (Table 4). When markers between these two survival groups were compared, we found that tumors associated with poor survival had a strong trend towards having higher total c-MET level compared to those with better survival ( p = 0.05), resonating previous report showing c-MET to be frequently overexpressed and represents an independent poor prognostic factor in resected PDAC patients [18, 19]. Interestingly, patients with poor survival had significantly lower levels of p-SHC ( p = 0.002), p-PRAS40 (p = 0.002) and p-AKT ( p = 0.025).…”
Section: Resultssupporting
confidence: 86%
“…First, high level of c-MET immunohistochemical staining in resected PDAC tumors has already been reported by different groups to be a poor prognostic marker [18, 19]. Second, to further confirm this finding, we performed c-MET IHC staining on an independent PDAC tissue microarray built at our institution.…”
Section: Resultssupporting
confidence: 59%
“…Immunohistochemical staining and evaluation of protein expression were performed on TMA as previously described. [9][10][11][12][13][14] DNA Panel Sequencing DNA was extracted from the same 279 samples that were also used for transcriptome microarrays. Sequencing libraries were prepared using Ion AmpliSeq Cancer HotSpot Panel, version 2 (Life Technologies) by following the manufacturer's recommendations.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Several clinical studies have addressed these issues and reported MET aberrations as indicators of short survival and clinicopathological features of advanced disease in diverse types of cancer, such as gastric [52], colorectal [53], breast [54], hepatocellular [55], pancreatic [56], and lung cancer [57]. In addition, the predictive role of MET dysregulation has been explored in different settings, and some results indicate improved Figure 2.…”
Section: I-a-the Importance Of Hgf/met Aberrations As Clinical Biomarmentioning
confidence: 99%